2021
DOI: 10.1093/noajnl/vdab156
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II trial of efficacy and safety of the immunotherapy ALECSAT as an adjunct to radiotherapy and temozolomide for newly diagnosed glioblastoma

Abstract: Background There is an urgent need for effective treatments against glioblastoma (GBM). In this trial we investigated the efficacy and safety of an adoptive cell-based immunotherapy. Methods Patients with newly diagnosed GBM were recruited at four study sites in Sweden. The patients were randomized 1:2 to receive either radiotherapy (RT), 60 Gy/30 fractions, with concomitant and adjuvant temozolomide (TMZ) only, or RT and TMZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Overall, there were conflicting survival results for adoptive cell therapies. A randomised open-label phase III trial of intravenous autologous cytokine-induced killer cells in 180 patients reported prolonged PFS but not OS in treated patients (126); a randomised phase II trial of autologous lymphoid effector cells specific against tumour (ALECSAT) in 62 patients found no significant survival difference between treated and control patients (127). A further non-randomised phase I study conducted by Smith et al (128) reported favourable survival in 25 patients treated with autologous cytokine-specific T cells; patients treated before recurrence had significantly improved OS than patients who had progressed.…”
Section: Other Immunotherapiesmentioning
confidence: 99%
“…Overall, there were conflicting survival results for adoptive cell therapies. A randomised open-label phase III trial of intravenous autologous cytokine-induced killer cells in 180 patients reported prolonged PFS but not OS in treated patients (126); a randomised phase II trial of autologous lymphoid effector cells specific against tumour (ALECSAT) in 62 patients found no significant survival difference between treated and control patients (127). A further non-randomised phase I study conducted by Smith et al (128) reported favourable survival in 25 patients treated with autologous cytokine-specific T cells; patients treated before recurrence had significantly improved OS than patients who had progressed.…”
Section: Other Immunotherapiesmentioning
confidence: 99%
“…It can pass through the blood–brain barrier, and its bioavailability is close to 100% [ 3 ]. It has also been used clinically, and can effectively treat newly diagnosed and relapsed glioblastomas and anaplastic astrocytomas, prolong the survival period of patients, and has good safety and tolerance [ 117 ]. However, overall, the efficacy of TMZ does not satisfy the majority of patients.…”
Section: Nf-κb Activation Is Involved In Development and Progression ...mentioning
confidence: 99%